Emergency medical admissions, deaths at weekends and the public holiday effect. Cohort study. Issue 1 (23rd January 2013) - Smith, Stacy; Allan, Ananda; Greenlaw, Nicola; Finlay, Sian; Isles, Chris
Abstract : Objectives: To assess whether mortality of patients admitted on weekends and public holidays was higher in a district general hospital whose consultants are present more than 6 h per day on the acute medical unit with no other fixed clinical commitments. Design: Cohort study. Setting: Secondary care. Participants: All emergency medical admissions to Dumfries and Galloway Royal Infirmary between 1 January 2008 and 31 December 2010. Methods: We examined 7 and 30 day mortality for all weekend and for all public holiday admissions, using all weekday and non-public holiday admissions, respectively, as comparators. We adjusted mortality for age, gender, comorbidity, deprivation, diagnosis and year of admission. Results: 771 (3.8%) of 20 072 emergency admissions died within 7 days of admission and 1780 (8.9%) within 30 days. Adjusted weekend mortality in the all weekend versus all other days analysis was not significantly higher at 7 days (OR 1.10, 95% CI 0.92 to 1.31; p=0.312) or at 30 days (OR 1.07, 95% CI 0.94 to 1.21; p=0.322). By contrast, adjusted public holiday mortality in the all public holidays versus all other days analysis was 48% higher at 7 days (OR 1.48, 95% CI 1.12 to 1.95; p=0.006) and 27% higher at 30 days (OR 1.27, 95% CI 1.02 to 1.57; p=0.031). Interactions between the weekend variable and the public holiday variable were not statistically significant for mortality at either 7 or 30 days. Conclusions: Patients admitted as emergencies to medicine on public holidays had significantly higher mortality at 7 and 30 days compared with patients admitted on other days of the week.